Lipid biomarkers in Holocene and glacial sediments from ancient Lake Ohrid (Macedonia, Albania) - J. Holtvoeth; H. Vogel; B. Wagner; G. A. Wolff (Biogeosciences, 2010)
Organic matter preserved in Lake Ohrid sediments originates from aquatic and terrestrial sources. Its variable composition reflects climate-controlled changes in the lake basin's hydrology and related organic matter export, i.e. changes in primary productivity, terrestrial plant matter input and soil erosion. Here, we present first results from lipid biomarker investigations of Lake Ohrid sediments from two near-shore settings: site Lz1120 near the southern shore, with low-lying lands nearby and probably influenced by river discharge, and site Co1202 which is close to the steep eastern slopes. Variable proportions of terrestrial n-alkanoic acids and n-alkanols as well as compositional changes of ω-hydroxy acids document differences in soil organic matter supply between the sites and during different climate stages (glacial, Holocene, 8.2 ka cooling event). Changes in the vegetation cover are suggested by changes in the dominant chain length of terrestrial n-alkanols. Effective microbial degradation of labile organic matter and in situ contribution of organic matter derived from the microbes themselves are both evident in the sediments. We found evidence for anoxic conditions within the photic zone by detecting epicholestanol and tetrahymanol from sulphur-oxidising phototrophic bacteria and bacterivorous ciliates and for the influence of a settled human community from the occurrence of coprostanol, a biomarker for human and animal faeces (pigs, sheep, goats), in an early Holocene sample. This study illustrates the potential of lipid biomarkers for future environmental reconstructions using one of Europe's oldest continental climate archives, Lake Ohrid.